Hyperactivation of Wnt/β-catenin and Jak/Stat3 pathways in human and zebrafish foetal growth restriction models: Implications for pharmacological rescue - Risato, Giovanni; Celeghin, Rudy; Brañas Casas, Raquel; Dinarello, Alberto; Zuppardo, Alessandro; Vettori, Andrea; Pilichou, Kalliopi; Thiene, Gaetano; Basso, Cristina; Argenton, Francesco; Visentin, Silvia; Cosmi, Erich; et al. (Frontiers in Cell and Developmental Biology, 2022)
Foetal Growth Restriction (FGR), previously known as Intrauterine Growth Restriction (IUGR), is an obstetrical condition due to placental insufficiency, affecting yearly about 30 million newborns worldwide. In this work, we aimed to identify and pharmacologically target signalling pathways specifically involved in the FGR condition, focusing on FGR-related cardiovascular phenotypes. The transcriptional profile of human umbilical cords from FGR and control cases was compared with the response to hypoxia of zebrafish (Danio rerio) transgenic lines reporting in vivo the activity of twelve signalling pathways involved in embryonic development. Wnt/β-catenin and Jak/Stat3 were found as key pathways significantly dysregulated in both human and zebrafish samples. This information was used in a chemical-genetic analysis to test drugs targeting Wnt/β-catenin and Jak/Stat3 pathways to rescue a set of FGR phenotypes, including growth restriction and cardiovascular modifications. Treatments with the Wnt/β-catenin agonist SB216763 successfully rescued body dimensions, cardiac shape, and vessel organization in zebrafish FGR models. Our data support the Wnt/β-catenin pathway as a key FGR marker and a promising target for pharmacological intervention in the FGR condition.